Radiation therapy for intracranial tumours in cats with neurological signs. Issue 8 (August 2019) - Körner, Maximilian; Roos, Malgorzata; Meier, Valeria S; Soukup, Alena; Cancedda, Simona; Parys, Magdalena M; Turek, Michelle; Rohrer Bley, Carla
Objectives: The aim of this study was to evaluate the outcome of cats with intracranial tumours presenting with neurological signs treated with radiation therapy. Methods: This study comprised a retrospective multicentre case series. Medical records of a total of 22 cats with intracranial space-occupying lesions, presenting with neurological signs and/or epileptic seizures and treated with external beam radiation therapy, were reviewed. In the treated cats, patient-, tumour- and treatment-related variables were investigated, including age, sex, tumour location, tumour volume, total radiation dose, equivalent dose in 2 Gy fractions (EQD2 ), corticosteroid dose, overall treatment time and institution for influence on local tumour control and survival. Results: Based on advanced imaging characteristics, the 22 treated cats presented with meningioma (n = 11), pituitary tumour (n = 8), choroid plexus tumour (n = 2) or glioma (n = 1). Allocated to the neuraxis, 11 lesions were extra-axial, three were intra-axial and eight were located in the pituitary region. At diagnosis, 21 cats exhibited altered neurological status. One cat presented with epileptic seizures and another cat had both seizures and altered neurological status. The mean total physical dose of radiation was 41.63 Gy (± 4.33), range 24–45 Gy. In all but one cat (95.5%), neurological signs improved after radiation therapy. The median progression-free survival was 510 days (95% confidence interval [CI]: 51–969). The proportion free of progression at 1 year was 55.7% (95% CI: 33–78). Fourteen cats died (only in five cases was death related to the intracranial tumour) and eight cats were still alive or lost to follow-up. The median overall survival time was 515 days (95% CI: 66–964). None of the tested variables influenced outcome. Conclusions and relevance: Radiation therapy seems to represent a viable treatment option in cats with intracranial tumours, relieving neurological signs and improving local tumour control. Radiation therapy may be considered for cats with tumours in complicated/inoperable localisations or for cases with a high peri- and postoperative risk.